PENGARUH METIL SELULOSA 4000 DAN PROPILEN GLIKOL TERHADAP STABILITAS FISIK GEL VITAMIN C - Anita Nilawati; Tn. Saifullah Sulaiman; Ediati Sasmita (Jurnal Farmasi Indonesia, 2015)
Vitamin C is an antioxidant and it’s usefull to prevent skin from free radicals damage. Vitamin C gel is preferably because it is not sticky, easy to spread, and not leaving oily texture on skin. Methyl cellulose 4000 can influence viscosity and propylene glycol is a cosolvent with dielectrict constant lower than water, this 2 factors can increase the stability of vitamin C gel. This study aimed to optimize and evaluate the influence of methyl cellulose 4000 and propylene glycol to physical stability and antioxidant activity of vitamin C gel. A 22 factorial design was applied to optimize the vitamin C gel using methyl cellulose 4000 and propylene glycol as independent variables. Each factor had 2 levels i.e 2% and 3% for methyl cellulose 4000, 10% and 20% for propylene glycol. The results showed that methyl cellulose 4000 and propylene glycol influence the physical stability and antioxidant activity of vitamin C gel. Increasing concentration methyl cellulose 4000 had increase the viscosity and stickability, and at the other hand decrease spreadability and viscosity changes. Increasing propylene glycol concentration had increase viscosity.